Procesy dostosowawcze przedsiębiorstwa rolniczego do warunków działalności - Kapusta, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Used method of analysis enabled to detect adapting methods to changing environment of operation. In the analysed period, following changes have taken place: The agricultural co-operative productive society was passing the process of restructuring in Rostkowice between 1992 and 2002 like other economic subjects in agriculture. Reducing the number of members of co-operatives and employment occurred, when simultaneous increasing the area for agriculture and of production volume. Increasing the labour productivity and decrease in expenses were a consequence of this action of work. Rationalization of expenditure of current assets also occurred (of mineral fertilizers, concise fodders, the fuel) and of investment activity. The organization of vegetable production was heading towards narrowing the assortment of production. A concentration was occurring on cultivation of the wheat, rape and sugar beets. Remaining cultivation is playing the marginal part. It is occurring in animal production on the basis for own breeding of piglets and purchase within the confines of the co-operation from individual farmers. The co-operative is marked by the constant tendency towards the improvement in production and financial effects, nonetheless weaknesses are also occurring here what a pointer analysis showed. Strong points aren't being utilized completely for the co-operative. A need for running chances and the elimination from preservation of outlets of resulting threats is occurring. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 147-155